Research and practice on working flow engine of big data platform for gaming service - Jie CHEN; Juan WU; Yang SU; Yong TANG (Dianxin kexue)
The big data platform for gaming service is based on Hadoop open source technology. With the demand growth of the service operation staff，there are more and more jobs which depend on each other running on the big data platform. A new working flow engine was developed on Zeus to manage and schedule jobs efficiently. In order to shorten the start time，Zeus task starting process was optimized and multi-threaded start task was achieved. Zeus was also improved to support the Oracle stored procedure. Pipeline technology was used to seamless and efficient sharing and transmission of heterogeneous data sources.